Online Learning Evaluation in Higher Education: Study Survey Method - Wijaya, Hengki; Sumule, Leonard; Weismann, Ivan Th. J.; Supartini, Tri; Tari, Ezra (Journal of Education Technology, 2021)
The challenge of online learning for students is the lack of direct interaction between students and lecturers, causing students to have difficulty learning. In addition, unstable internet network constraints cause the learning process not to run optimally. This paper aims to develop online learning in universities. The type of research is a descriptive survey. The research respondents were 96 students. This study examines the effectiveness of the online learning process. Data were analyzed and compared with research results in journal articles. The online learning evaluation analysis from the side of the first student showed that students were more interested in face-to-face learning than online. Second, most students plan to study now for future use. Third, the main obstacles faced by students are internet access and internet quota. Lecturers have an essential role in helping students learn online. Third, students need groups to share the happy learning process. Thus, the readiness of lecturers and students in online learning needs to be improved with the support of learning technology devices.